Higher risk of tuberculosis in combination therapy for inflammatory bowel disease: A nationwide population-based cohort study in South Korea. Issue 44 (30th October 2020) - Choi, Seong Ji; Kim, Min Sun; Kim, Eun Sun; Lee, Juneyoung; Lee, Jae Min; Choi, Hyuk Soon; Keum, Bora; Jeen, Yoon Tae; Lee, Hong Sik; Chun, Hoon Jai; Kim, Chang Duck
Abstract : Abstract: Inflammatory bowel disease (IBD) in Asia has become increasingly prevalent. As a treatment of IBD, many immunomodulators and biological agents were introduced and shown to be effective in inducing and maintaining remission. However, many cases with treatment failure were reported. To overcome the failure, combination therapy of immunomodulatory and biologics have emerged, showing better outcomes by optimizing biologic pharmacokinetics and minimizing immunogenicity. Adversely, rates of tuberculosis (TB) have been increased as a result. The aim of this study is to compare the risk of TB according to the therapy using large population data. We used data from the South Korean Health Insurance and Review Agency over the period 2008–2016 and calculated the hazard ratio (HR) for TB in IBD. We compared the risk of TB according to the medication: infliximab only, azathioprine only (AZA), combination of azathioprine and infliximab (CAI), azathioprine monotherapy and infliximab monotherapy (AIM), and azathioprine and infliximab whether simultaneously or separately (AISS). In IBD patients, a total of 249 patients were identified as active TB. After one-to-one matching with age, sex and disease duration, the risks of TB were significantly higher in AZA group (HR, 2.06; 95% CI, 1.35–3.12, P  < .001), AIM group (HR, 3.26; 95% CI, 1.18–9.05, P  = .02), AISS group (HR, 3.50; 95% CI, 1.92–6.37, P  < .001), and CAI group (HR, 5.67; 95% CI, 2.42–10.21, P  < .001), and the HR increased gradually in this order. In UC patients, the results were in similar pattern, but this pattern was not observed in CD patients in our study. Our study shows that Korean IBD patients are at risk of TB, and the risk increases with usage of IBD medication; moreover, the risk is the highest if combination therapy is used. These results highlight the importance of screening for TB in IBD patients, especially in combination therapy.